Impact testing of snowboarding wrist protectors - Adams, C.; Allen, T.; Senior, T.; James, D.; Hamilton, N. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2023)
The wrist is a common injury site for snowboarders who often fall onto an outstretched hand. Wrist protectors are worn by some snowboarders to prevent wrist injuries by attenuating impact forces and limiting wrist extension. This paper presents a bespoke pendulum test device for impacting wrist protectors when fitted to a wrist surrogate. The rig can replicate injury risk scenarios, while measuring temporal forces and wrist extension angles. Results from testing 12 snowboarding wrist protectors are presented, including differences in peak vertical force, the time to reach this peak, and energy absorption between products. When compared to an unprotected surrogate, all 12 products lowered the peak force by at least 24% and increased the time to reach this peak by at least 1.8 times. Due to the severity of the load case employed, none of the products lowered the impact force below 2.8 kN, which is the value presented in the literature to fracture a cadaveric wrist. The developed rig could be used to support the development of new wrist protectors, as well as the development of finite element models for predicting wrist protector performance.